Choosing endotracheal tube size in children: Which formula is best?. (July 2020) - Manimalethu, Ria; Krishna, Senthil; Shafy, Shabana Z.; Hakim, Mohammed; Tobias, Joseph D.
Abstract: Objectives: Various formulae have been suggested to calculate the appropriate sized endotracheal tube in children. The current study prospectively compares three commonly used formulae for selection of cuffed endotracheal tubes in children. Methods: Patients were randomized to one of three formulae (Duracher, Cole, or Khine) to determine the size of the cuffed endotracheal tube for endotracheal intubation. The fit of the tube was noted and intracuff pressure was measured using a manometer. The postoperative incidence of stridor, throat pain/soreness, and hoarseness was noted in the post-anesthesia care unit at 2, 4 and 24 h after the procedure. Results: The study cohort included 135 patients less than or equal to 8 years, equally divided into three groups based on age, weight, and gender. There was no difference in the intracuff pressure, the volume required to seal the airway, or the number of times in which the intracuff pressure was greater than or equal to 20 or 30 cm H2 O among the three groups. Six tube changes were required in the Cole group while no tube changes were required in the Duracher group (p < 0.05). The postoperative incidence of adverse events (throat pain, hoarseness, and stridor) at 0–2 h, 2–4 h, and 24 h was higher in the Cole group when compared to the Duracher group. Conclusion: When using an endotracheal tube with a polyurethane cuff, the Duracher formula provided the best estimate for choosing the correct size.